A comparative study of oxygenated additives for diesel in compression ignition engine. (2018) - Kumar, Chandan; Rana, K.B.; Tripathi, B.; Nayyar, Ashish
Performance improvement and emissions control are quite difficult to handle simultaneously in diesel engines. These two tasks can be achieved by one of the methods such as: engine design improvement, engine exhaust treatment and modification in fuel. The modification of fuel using additives is most feasible approach to control the high emissions without deteriorating the engine performance. The aim of this paper is to present the comprehensive review and comparative study of oxygenated additives with respect to engine performance and emission characteristics. It is concluded from literature review that oxygenated compounds are the most suitable and economical among all additives available for this purpose.